2022-RA-1072-ESGO Optimal cytoreduction for advanced epithelial ovarian cancer: non invasive predictive factors. (20th October 2022) - Candotti, Giorgio; Bergamini, Alice; Cioffi, Raffaella; de Marzi, Patrizia; Filippo, Marianna Di; Galli, Federica; Rabaiotti, Emanuela; Sabetta, Giulia; Saponaro, Costanza; Vasta, Francesca; Bocciolone, Luca
Abstract : Introduction/Background: Standard treatment for advanced ovarian cancer patients should be primary cytoreduction followed by platinum-based chemotherapy. The aim of surgical effort should be the complete removal of all macroscopic disease. Prediction of post-operative residual disease after ovarian cancer cytoreductive surgery remains a topic of interest to gynecologic oncologists. The aim of this study was to evaluate non-invasive predictive factors for optimal cytoreduction. Methodology: From June 2018 to August 2021, 161 patients underwent cytoreductive surgery for advanced ovarian cancer at San Raffaele Hospital. Primary or interval debulking surgery (IDS) were included. Clinical, surgical, pathological and hematological parameters were recorded. 120 patients were eligible for this study. Results: Median age was 65 (range 32–84) years. Median hospital stays were 6 (range 2–32) days. Seventy-five patients (62, 5%) obtained optimal cytoreduction with absence of macroscopic disease. Eighty (67%) patients underwent PDS and 40 (33%) underwent IDS. Using a receiver operating characteristic analysis, cut-off values of Sodium and Neutrophil-Lymphocyte ratio (NLR) could be defined. This model had a sensitivity of 64% and specificity of 93% to predict optimal debulking surgery. Moreover, age over 70 and Emergency room access were independent factor to undergo to IDS. Conclusion: Age over 70 and Emergency room access could benefit IDS after Neoadjuvant Chemotherapy (NACT) to achieve RT=0. Level of sodium and NLR could use to predict optimal debulking surgery.